Measuring the level of upholding the national language among institute of higher education students [Pengukuran tahap pemartabatan bahasa kebangsaan dalam kalangan mahasiswa institusi pengajian tinggi] - Tohar S.N.A.M.; Halim A.A.; Samsu K.H.K. (Universiti Kebangsaan Malaysia Press, 2024)
The primary role of language in a multiethnic society is to be an instrument of solidarity that unite people of various races through the sharing of thoughts, world views and cultures based on a country's national identity. However, the issue of upholding the rightful position of the national language in Malaysia is still on-going, whether at the level of the policy makers or that of the masses. Therefore, there is a need to identify the actual level of the national language in the present scenario in terms of three aspects, namely i) fluency, ii) recognition, and iii) sophistication in the use of the language. Hence, a study was conducted among 407 students of University of Malaya (UM), Universiti Putra Malaysia (UPM), University of Selangor (UNISEL) and Multimedia University (MMU) using the Stratified Random Sampling method. The results of the analysis showed that the levels of fluency and recognition of the Malay language among IHE students are high. However, the level of sophistication in their use of the language is moderate. In fact, the overall ranking of the national language is also moderate. Thus, although the IHE students are fluent and they do recognise the national language, their levels of fluency and recognition are not very high. Instead, they have not fully mastered their skills in poetry, pantun and the use of proverbs, which are the benchmarks of sophistication in the use of the language. The implication is that after almost six decades of Malay language being formulated as the national language in the Federal Constitution, this language has yet to achieve its rightful position as a language that is not only being fluently spoken and recognised as the national language, but that is able to add to the aesthetic beauty of a language to show that it has its own level of dignity.Therefore, the scenario of upholding the national language in its rightful position among IHE students cannot be taken lightly because this generation will determine the pattern of stable social relations and the vitality of the national language in the civilization of Malaysia. 2017, Universiti Kebangsaan Malaysia Press. All rights reserved.